Quality Improvement of the Ammoniated Corn Husk through the Use of MA-11 Inoculant at Different Doses - Amin, Muhamad; Putra, Ryan Aryadin; Yanuarianto, Oscar; Noersidiq, Azhary; Suhubdy, Suhubdy; Dilaga, Syamsul Hidayat (Jurnal Agripet, 2025)
The research objective was to study the effect of different doses of MA-11 inoculants on improving the quality of ammoniated corn husks. The materials used were corn husks, urea, and the MA-11 inoculant. The research was conducted using Completely Randomized Design (CRD) with four treatments and three replications. The four treatments were T0: Ammoniated corn husks + 0% MA-11 (control), T1: Ammoniated corn husks + 0.5% MA-11, T2: Ammoniated corn husks + 1% MA-11, and T3: Ammoniated corn husks + 1.5% MA-11. The observed variables were chemical composition (dry matter, organic matter, crude protein, crude fiber, ether extract, and TDN), fiber components (NDF, ADF, cellulose, hemicellulose, and lignin), and in-vitro digestibility (dry matter and organic matter digestibility). The data obtained were analyzed by analysis of variance and further tested by Duncan's multiple range test. The results showed that the treatments had significantly different effects (P0.05) on chemical composition, fiber fractions, and digestibility. The 0.5% (T1) dosage rate yielded the best results for CP (7.25%), and TDN (56.88%); and achieved the greatest reduction in CF (28.57%) and ADF (42.90%) content. Conversely, the 1.5% (T3) dosage rate was optimal for EE (1.16%), DMD (43.23%), and OMD (43.90%). While all inoculation levels (0.5% to 1.5%) were also effective in reducing the NDF, cellulose, hemicellulose, and lignin fractions, whereas the highest (P0.05) Dry Matter and Organic Matter content was observed in the control (T0). It was concluded that different doses of the MA-11 inoculant had varied and specific effects on the nutritional parameters of ammoniated corn husk.